Effects of abscisic acid and xanthoxin on elongation and gravitropism in primary roots of Zea mays - Lee, J S (Plant science : an international journal of experimental plant biology, 1990)
We examined the involvement of abscisic acid (ABA) and xanthoxin (Xan) in maize root gravitropism by (1) testing the ability of ABA to allow positive gravitropism in dark-grown seedlings of the maize cultivar LG11, a cultivar known to require light for positive gravitropism of the primary root, (2) comparing curvature in roots in which half of the cap had been excised and replaced with agar containing either ABA or indole-3-acetic acid (IAA), (3) measuring gravitropism in roots of seedlings submerged in oxygenated solutions of ABA or IAA and (4) testing the effect of Xan on root elongation. Using a variety of methods of applying ABA to the root, we found that ABA did not cause horizontally-oriented primary roots of dark-grown seedlings to become positively gravitropic. Replacing half of the root cap of vertically oriented roots with an agar block containing ABA had little or no effect on curvature relative to that of controls in which the half cap was replaced by a plain agar block. Replacement of the removed half cap with IAA either canceled or reversed the curvature displayed by controls. When light-grown seedlings were submerged in ABA they responded strongly to gravistimulation while those in IAA did not. Xan (up to 0.1 mM) did not affect root elongation. The results indicate that ABA is not a likely mediator of root gravitropism and that the putative ABA precursor, Xan, lacks the appropriate growth-inhibiting properties to serve as a mediator of root gravitropism